Cooperative Localisation of a GPS-Denied UAV using Direction-of-Arrival Measurements - Russell, James S; Ye, Mengbin; Anderson, Brian DO; Hmam, Hatem; Sarunic, Peter (IEEE, 2019)
A GPS-denied UAV (Agent B) is localised through INS alignment with the aid of a nearby GPS-equipped UAV (Agent A), which broadcasts its position at several time instants. Agent B measures the signals' direction of arrival with respect to Agent B's inertial navigation frame. Semidefinite programming and the Orthogonal Procrustes algorithm are employed, and accuracy is improved through maximum likelihood estimation. The method is validated using flight data and simulations. A three-agent extension is explored.